Development and evaluation of ivabradine microspheres for controlled release. Issue 1 (25th April 2017) - Majeed, Abdul; Ranjha, Nazar Muhammad; Rasool, Muhammad Fawad; Hussain, Musaddique
Abstract : The objective of this study was to formulate and evaluate controlled release formulations of ivabradine hydrochloride (HCl)-loaded microspheres consisting of Kollicoat MAE 100 P and ethyl cellulose prepared by the oil-in-oil solvent evaporation method. The drug was encapsulated into microspheres by an in situ method by varying the polymer contents. The resultant microspheres were characterized with respect to drug loading, flow properties, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffractometry (XRD), thermal analysis and release behavior. Chemically stable loaded microspheres were confirmed by FTIR, differential scanning calorimetry (DSC), thermogravimetric analysis and XRD. SEM images showed that the microspheres were spherical with smooth surfaces. FTIR spectra confirmed the presence of the drug in pure form and revealed no interaction between the drug and polymers. XRD and DSC were conducted to determine the nature of the drug in drug-loaded microspheres, and the results revealed that the drug was present in amorphous form. The maximum percentage entrapment efficiency was found to be 82 ± 2·11%, and the percentage yield was 89 ± 3·31%. The maximum in vitro drug release was more than 90% for pH 7·4, which demonstrated that drug-loaded formulations had a pH-dependent drug release. Cumulative drug release data were analyzed by using different kinetic models. The Korsmeyer–Peppas equation was used to determine the value of n which follows non-Fickian diffusion.